Transplantation of Induced Pluripotent Stem Cell‐Derived Neural Stem Cells Mediate Functional Recovery Following Thoracic Spinal Cord Injury Through Remyelination of Axons. (15th May 2015) - Salewski, Ryan P.; Mitchell, Robert A.; Li, Lijun; Shen, Carl; Milekovskaia, Maria; Nagy, Andras; Fehlings, Michael G.
Abstract : Neural stem cells (NSCs) from embryonic or fetal/adult tissue sources have shown considerable promise in regenerative strategies for traumatic spinal cord injury (SCI). However, there are limitations with their use related to the availability, immunogenicity, and uncertainty of the mechanisms involved. To address these issues, definitive NSCs derived from induced pluripotent stem (iPS) cells generated using a nonviral, piggyBac transposon approach, were investigated. Committed NSCs were generated from iPS cells using a free‐floating neurosphere methodology previously described by our laboratory. To delineate the mechanism of action, specifically the role of exogenous myelination, NSCs derived from wildtype ( wt ) and nonmyelinating Shiverer ( shi ) iPS cell lines were used following thoracic SCI with subacute intraspinal transplantation. Behavioral, histological, and electrophysiological outcomes were analyzed to assess the effectiveness of this treatment. The wt‐ and shi‐ iPS‐NSCs were validated and shown to be equivalent except in myelination capacity. Both iPS‐NSC lines successfully integrated into the injured spinal cord and predominantly differentiated to oligodendrocytes, but only the wt‐ iPS‐NSC treatment resulted in a functional benefit. The wt ‐iPS‐dNSCs, which exhibited the capacity for remyelination, significantly improved neurobehavioral function (Basso Mouse Scale and CatWalk), histological outcomes, and electrophysiological measures of axonal function (sucrose gap analysis) compared with the nonmyelinating iPS‐dNSCs and cell‐free controls. In summary, we demonstrated that iPS cells can generate translationally relevant NSCs for applications in SCI. Although NSCs have a diverse range of functions in the injured spinal cord, remyelination is the predominant mechanism of recovery following thoracic SCI. Significance: Gain‐of‐function/loss‐of‐function techniques were used to examine the mechanistic importance of graft‐derived remyelination following thoracic spinal cord injury (SCI). The novel findings of this study include the first use of neural stem cells (NSCs) from induced pluripotent stem cells (iPSCs) derived using the clonal neurosphere expansion conditions, for the treatment of SCI, the first characterization and in vivo application of iPSCs from Shiverer mouse fibroblasts, and the first evidence of the importance of remyelination by pluripotent‐sourced NSCs for SCI repair and regeneration. Abstract : This study examined the mechanistic importance of graft‐derived remyelination following thoracic spinal cord injury (spinal cord injury), thereby providing the first use of neural stem cells (NSCs) derived from induced pluripotent stem cells (iPSCs) using the clonal neurosphere expansion conditions for treatment of SCI, the first characterization and in vivo application of iPSCs from Shiverer mouse fibroblasts, and the first evidence of the importance of remyelination by pluripotent‐sourced NSCs for SCI repair and regeneration.